2020
DOI: 10.2151/jmsj.2020-027
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Seasonal Transitions of ENSO on Atmospheric River Activity over East Asia

Abstract: This pre-publication manuscript may be downloaded, distributed and used under the provisions of the Creative Commons Attribution 4.0 International (CC BY 4.0) license. It may be cited using the DOI below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…It was also reinforced by the low-level flows from the south, similar to previous events in Japan (e.g., Hirota et al, 2016;Tsuguti et al, 2019). Meanwhile, it is likely that the westward extension of the western Pacific Subtropical High (WPSH) also enhanced the northward moisture transport from the SCS to Japan (e.g., Naoi et al, 2020).To date, the relationship between moisture transport and heavy rainfall during the Baiu season has been extensively studied (e.g., Kamae et al, 2017;Zhou & Yu, 2005). Previous studies demonstrated that the strong precipitation is primarily related to the local moisture convergence, accompanied by the low-level southerly…”
supporting
confidence: 67%
See 1 more Smart Citation
“…It was also reinforced by the low-level flows from the south, similar to previous events in Japan (e.g., Hirota et al, 2016;Tsuguti et al, 2019). Meanwhile, it is likely that the westward extension of the western Pacific Subtropical High (WPSH) also enhanced the northward moisture transport from the SCS to Japan (e.g., Naoi et al, 2020).To date, the relationship between moisture transport and heavy rainfall during the Baiu season has been extensively studied (e.g., Kamae et al, 2017;Zhou & Yu, 2005). Previous studies demonstrated that the strong precipitation is primarily related to the local moisture convergence, accompanied by the low-level southerly…”
supporting
confidence: 67%
“…It was also reinforced by the low‐level flows from the south, similar to previous events in Japan (e.g., Hirota et al., 2016; Tsuguti et al., 2019). Meanwhile, it is likely that the westward extension of the western Pacific Subtropical High (WPSH) also enhanced the northward moisture transport from the SCS to Japan (e.g., Naoi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown ARs are related to precipitation extremes, flooding, seasonal snowpack, and water availability in the western United States and western Europe (Ralph et al 2006;Guan et al 2010;Dettinger 2011;Guan et al 2013;Lavers and Villarini 2013;Wick et al 2013). Moreover, ARs modulate extreme precipitation and anomalous snow accumulation in many other regions including Antarctica (Gorodetskaya et al 2014;Bozkurt et al 2018;Gorodetskaya et al 2020), Australia and New Zealand (Kingston et al 2016;Ye et al 2020;Prince et al 2021;Reid et al 2021), the Arctic Ocean and Greenland (Baggett et al 2016;Hegyi and Taylor 2018;Mattingly et al 2018;Neff 2018;Wernli and Papritz 2018;Wille et al 2019;Mattingly et al 2020), South America (Viale and Nunez 2011;Viale et al 2018;Ramos et al 2019), North Africa (Blamey et al 2018;Akbary et al 2019;Dezfuli 2020;Massoud et al 2020), and East Asia (Naoi et al 2020;Pan and Lu 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Synoptic‐scale atmospheric circulation anomalies resulting from teleconnections associated with those major modes of climate variability have often been linked to extreme precipitation. For example, extreme rainfall associated with atmospheric rivers in East Asia increases during the post‐El Niño summer with the enhancement of water vapor fluxes (Kamae et al., 2017; Naoi et al., 2020). Typhoons, another cause of heavy rain in the western north Pacific region, are also known to change their tracks depending on ENSO and associated large‐scale atmospheric circulation anomalies (Camargo et al., 2007; Kim et al., 2011).…”
Section: Introductionmentioning
confidence: 99%